2001
DOI: 10.1073/pnas.171185198
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the transcriptome of the malaria sporozoite stage

Abstract: Most studies of gene expression in Plasmodium have been concerned with asexual and͞or sexual erythrocytic stages. Identification and cloning of genes expressed in the preerythrocytic stages lag far behind. We have constructed a high quality cDNA library of the Plasmodium sporozoite stage by using the rodent malaria parasite P. yoelii, an important model for malaria vaccine development. The technical obstacles associated with limited amounts of RNA material were overcome by PCR-amplifying the transcriptome befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
89
0
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(100 citation statements)
references
References 45 publications
7
89
0
2
Order By: Relevance
“…B, Presence in independent blood stage specific proteomic or transcriptomic data sets: blood stage mass spectrometry, published (4, 7) and unpublished (Leiden Malaria group, www.PlasmoDB.org); blood stage EST (13); and experimentally infected or naturally exposed protein microarray data sets (3,14). and/or liver stage of the Pf parasite lifecycle by multidimensional protein identification technology (17), MS/MS (29,30), or EST expression analysis (31)(32)(33)(34)(35), validating our identification as putative sporozoite and/or liver stage antigens (supplementary Table S1). Likewise, almost all of the bloodstage specific antigens (91%, 21/23 proteins) have been previously identified in MS ((17, 36), Leiden group, unpublished), transcript (37) or protein array data sets (7,18).…”
Section: Discussionsupporting
confidence: 54%
“…B, Presence in independent blood stage specific proteomic or transcriptomic data sets: blood stage mass spectrometry, published (4, 7) and unpublished (Leiden Malaria group, www.PlasmoDB.org); blood stage EST (13); and experimentally infected or naturally exposed protein microarray data sets (3,14). and/or liver stage of the Pf parasite lifecycle by multidimensional protein identification technology (17), MS/MS (29,30), or EST expression analysis (31)(32)(33)(34)(35), validating our identification as putative sporozoite and/or liver stage antigens (supplementary Table S1). Likewise, almost all of the bloodstage specific antigens (91%, 21/23 proteins) have been previously identified in MS ((17, 36), Leiden group, unpublished), transcript (37) or protein array data sets (7,18).…”
Section: Discussionsupporting
confidence: 54%
“…MAEBL was identified in P. yoelii and P. falciparum blood stage parasites as a minor membrane protein with erythrocyte binding activity expressed in the apical organelles and on the surface of invasive merozoites [3][4][5][6]. Expressed abundantly in sporozoites, MAEBL appears to be important for sporozoite invasion into the mosquito salivary glands and in establishing exoerythrocytic schizonts [6][7][8][9][10][11][12]. It has been reported that sera from infected individuals living in a malaria endemic region of western Kenya recognized M2 recombinant antigen and had the ability to inhibit M2-erythrocyte binding [6].…”
Section: Malaria; Plasmodium Falciparum; Maebl; Erythrocyte Binding Pmentioning
confidence: 99%
“…Their products exhibit a predicted N-terminal cleavable signal peptide followed by two 6-Cys domains. In addition, P52 exhibits a C-terminal hydrophobic sequence predicted to be a putative GPI anchor attachment signal (15). PfP52 and PfP36 show 40% and 43% amino acid identity to their respective P. yoelii orthologs.…”
mentioning
confidence: 99%